Determining the number of fibre-fibre contacts in cardboard samples using tomographic imaging - Ekman, Axel (2011)
The fibrous network of cardboard samples was studied with the aid of tomographic imaging. For analysing the samples a method of determing the number of contacts between fibres in a planar fibrous network was introduced. The model is based on the fact that deposited paper-like structures tend to have predominantly planar fibre orientation. With this assumption an expression of the mean segment length was derived in terms of the average shortest path along fibres through the sample in the out-of-plane direction.